Pre-service teachers’ understanding of how learners can be developed and equipped with constitutional values when teaching Life Sciences topics - Ajayi, J.; Mavuru, L. (South African Journal of Higher Education, 2025)
Values education is value formation through education that is conveyed through educational goals usually set by curricular documents. Consistent with this, the National Curriculum Statement (NCS) Grades R–12, comprising the Curriculum Assessment and Policy Statement (CAPS), which is the currently used policy statement in South African schools, is underscored by a curriculum philosophy that urges teachers to “equip learners with values” during classroom teaching of all approved subjects. Hence, this study explored preservice teachers’ understanding of how learners can be developed and equipped with constitutional values when teaching Life Sciences topics. A perception–value (P–V) theoretical framework was adapted to underpin the qualitative study. Data were initially derived from the NCS Grades R–12, comprising the CAPS for Life Sciences. Also, through a case study methodology, data were collected from responses to a values–education–driven assignment given to 70 pre–services teachers as participants. Both data sets were analysed and interpreted using analytical approaches involving content and thematic analyses (Bowen 2009). Results show participants’ understanding regarding (i) identification of constitutional values incorporated in Life Sciences topics, either in correspondence with the content/concepts therein, or not; (ii) teaching strategies they can use to nurture the values identified in learners through classroom teaching of Life Sciences. Ultimately, this study created awareness of how teacher–educators could depict pre–service teachers’ understanding of the curriculum (NCS) philosophy of equipping learners with values. This may enhance teacher–educators’ understanding on how to teach pre–service teachers about using the teaching of Life Sciences concepts to foster values education.